2013
DOI: 10.1155/2013/561032
|View full text |Cite
|
Sign up to set email alerts
|

Severe Skin Forms of Psoriasis in Black Africans: Epidemiological, Clinical, and Histological Aspects Related to 56 Cases

Abstract: Bacground. Psoriasis is an erythematosquamous dermatosis of chronic development. In sub-Saharan Africa, few studies have been focused on complicated forms of psoriasis. Objective. The aim is to describe epidemiological, clinical, and histological features of severe skin forms of psoriasis in Cote d'Ivoire. Material and Methods. The study was both cross-sectional and descriptive, that focused on patient admitted to the dermatology unit for complicated psoriasis, from January 1st, 1986, to December 31th, 2007. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
9
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 16 publications
6
9
1
Order By: Relevance
“…In their study lymphocytic infiltrate (100%), dilated capillaries (63.6%) and tortuosity (36.6%) were the commonly observed dermal changes. 5 But the current study showed mixed inflammatory infiltrate as common type of dermal infiltration (66.67%).…”
Section: Discussioncontrasting
confidence: 50%
See 4 more Smart Citations
“…In their study lymphocytic infiltrate (100%), dilated capillaries (63.6%) and tortuosity (36.6%) were the commonly observed dermal changes. 5 But the current study showed mixed inflammatory infiltrate as common type of dermal infiltration (66.67%).…”
Section: Discussioncontrasting
confidence: 50%
“…This finding correlated with a cross-sectional study done by Kassi et al, where psoriasis vulgaris was found in 60.7% ,universal psoriasis in 37.5% and generalized pustular psoriasis in 1.8% among 56 patients. 5 Psoriasis was widely distributed in different age groups in the present study. The most common age was observed in second and fifth decades.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations